Bytes, Words, Texts: The Anglo-Norman Dictionary and its Text-Base - David Trotter (Digital Medievalist, 2012)
This paper summarizes how the Anglo-Norman Dictionary project has developed from an originally paper-based and print dictionary, to a fully digital, freely available online resource, comprising not only the Dictionary itself, but a substantial text-base in the same XML format as the Dictionary. The paper reviews the history of the Dictionary; the principles of structured encoding; the relationship between the citations (attestations) in the Dictionary, as instances of parole, and the broader Anglo-Norman language (the langue); and the detailed encoding of entries.